Lightweight Cryptographic Simulation of Power IoT Fused with Bayesian Network Algorithms - Zhu, Xueqiong; Hu, Chengbo; Lu, Yongling; Wang, Zhen; Xue, Hai (EAI Endorsed Transactions on Scalable Information Systems, 2023)
In the power system, the transmission and processing of information is a very important link, and the core part of it is electronic data, and the transmission and processing of electronic data is the most important link in the power system. Because information is continuously passed between network nodes, the security requirements for information are high. With the development of Internet technology, its application field has been widely expanded to various industries. Therefore, to better ensure power quality and improve network operation efficiency, it is necessary to rationally and effectively manage the entire communication system. Power Internet of Things technology combines information transmission and processing links and realizes data sharing between various communication nodes in the entire network system through intelligent management, thereby improving overall information security. This paper first introduces the research of Bayesian network algorithm, then studies the process of lightweight encryption implementation of power Internet of Things, and then simulates and compares various encryption algorithms to obtain the best encryption scheme, and finally verifies through simulation that the algorithm can effectively ensure the safe transmission of information and improve the efficiency of network operation.